Financing of Global Imbalances - Punzi, Maria Teresa (IMF Working Papers; Working Paper, 2007)
This paper analyzes the determinants of bond flows, now the dominant source of capital inflows, into the United States, as a means of establishing conditions affecting the financing of the U.S. current account deficit. To test the hypothesis that capital flows have become more responsive to changes in relative interest rates and other conditions across borders, a panel data set, showing bond flows from 12 separate jurisdictions into the United States, is constructed for the period 1994-2006 using adjusted U.S. Treasury International Capital Flow (TIC) data. Panel vector autoregression and instrumental variables approaches are used to estimate the impact of changes in interest rate differentials and other fundamentals on capital flows into the U.S. The paper finds evidence for an impact from interest rate differentials to bond inflows that has increased over time. Under one plausible set of theoretical assumptions, the increased sensitivity can be interpreted as resulting from a reduction in home bias on the part of non-US investors.